The Effect Of Facilities, Price, And Service Quality On Customer Satisfaction At Formosa Hotel Batam - Beby Sinsanto; Realize (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to determine the effect of facilities, prices and service quality on Formosa Hotel Batam customer satisfaction. In this study the population is all customers in Formosa Batam Hotel in June 2018 which amounted to 1455 customers. The sampling technique used is Probability Sampling, where sampling is calculated using Slovin formula with a problem level of 5% and get the results of 314 respondents and used as a sample in this study. Data collection techniques in this study used a questionnaire. The data collected were analyzed using multiple linear regression analysis with the help of SPSS (Product and Service Solution) calculation tool version 21. The results in this study indicate that from the results of the T-test, it is known that for independent variables namely facilities significantly influence customer satisfaction, prices have a significant effect on customer satisfaction, and service quality has a significant effect on customer satisfaction. The F test results of 27.482 are greater than f table of 3.02 with a significant value of 0.000 which is smaller than the value of α 0.05 indicating that facility variables, price variables and service quality variables jointly influence customer satisfaction.